Elephants in the Room : A Review to Reshape Future Research on Politically Connected Boards and Financial Performance - Lim, Keh Yee; Mohd Sabrun, Ibrahim; Nur Farrahanie, Ahmad Tarmizi; Noor Adwa, Sulaiman (Universiti Malaysia Sarawak, 2024)
Politically connected firms are prevalent worldwide, spurring political connection research. This systematic literature review (SLR) examines the current development in political connection research, specifically examining the impact of politically connected directors and CEOs (PCDCs) and corporate financial performance (CFP). This study conducts a bibliometric analysis of 247 articles from Scopus, spanning the years 2006 to 2023. Additionally, 52 high-quality articles are selected for further evaluation using content analysis under the Theory, Context, Characteristics, and Methodology (TCCM) framework. The findings reveal that Asian studies have predominated the body of literature. Through thematic analysis by the keywords, the conceptual structure of PCDC-CFP research is grouped into five distinct clusters. The literature review highlights that PCDCs may be a double-edged sword for CFP, with contradictory findings. This study delves into the geographical focus, theoretical perspectives and methodological arguments of previous research, thereby identifying potential room for future research to enrich the literature. The complex effects of PCDCs on CFP makes call for better policy and business decisions.